Electrobioremediation of Patagonian Soils Contaminated with Hydrocarbons - Pucci,G.N. (2012)
The electrokinetic technique is used to remediate hydrocarbon-contaminated soil. The aim of this paper is to evaluate the feasibility of using this technology to remediate oil- contaminated soils in the Gulf of San Jorge. The soils used in this experiment were unsaturated soils contaminated by oil field operations being carried out in the area and previously remediated by landfarming. A potential difference of 0.5V cm-1 was applied to the electroremediation cells for 120 days; bridges of phosphate salt were used for the cells. Total hydrocarbons decreased from 4.22% to 3%, modifying the percentages of aliphatic, aromatic and polar hydrocarbons. The pH changed from 7.96 to 8.6 and 7.1 in the cathode and anode, respectively. The final pH values were compatible with the degrading bacterial community, whose colony-forming numbers did not present any alteration. On the cathode, there was an increase in the percentage of Gram-positive bacteria. Most of the species isolated were identified as Microbacterium luteus.